Implementation of Guidelines And Counseling Services in Managing Student Discipline in SDN 2 Jogomertan - Lestari, Hesti; Lestari, Dwi Puji; Joharman, Joharman; Fatimah, Siti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
This article aims to describe, 1) Discipline program planning through guidance and counseling services at SDN 2 Jogomertan, 2) Implementation of disciplinary programs through guidance and counseling services at SDN 2 Jogomertan, 3) Evaluation of discipline programs through guidance and counseling services at SDN 2 Jogomertan . This research is a descriptive study with the object of 1 school principal, 10 teachers and employees, and 10 students in grades 4, 5, and 6. The data analysis technique uses a qualitative descriptive approach. The results of the study, 1) Program planning is poured in a plenary meeting with all student guardians, parents' group meetings of each class, and school routine meetings, 2) Planting student discipline including coming to school on time, literacy before starting learning, discipline in doing homework, discipline to maintain environmental cleanliness, and regular prayer in congregation. 3) Evaluation of disciplinary programs is carried out at every report on program implementation (in the form of program reports, evaluation reports and follow-up to program implementation)